Sport-specific training for a competitive freestyle sprint swimmer - Monu, J. M. (Strength and Conditioning Journal, 2013)
Sport-specific strength training for swimmers is achieved by performing exercises that stimulate the same muscles in the same manner as the swim. Sport-specific exercises can help increase strength, power, and body control and decrease the risk of shoulder injuries. When 100th of a second could determine first to third place, the purpose of this article was to develop a sport-specific strength training regimen for a competitive freestyle swimmer.